PRONUNCIATION ERRORS IN VOWELS BY VOCATIONAL SCHOOL STUDENTS - Ratna Dewi Br Ginting; Johan Sinulingga; Sortha Silitonga (Universitas Negeri Medan, 2017)
The aim of this study was to find out the pronunciation errors in long vowels in speaking test that have been made by the office administration and travel agency students SMK Negeri 1 Binjai. It was conducted by using qualitative research. The sample of this stufy is 30 students which is from office administration and travel agency students. The instrument of this research is speaking test that recorded in each student. The results shown the total errors in office administration students are 103 while in travel agency students are 118. The percentage of the error of office administration class is 47% and the percentage of the error of travel agency class is 53%. It shown that their ability in speaking test is still low. It was concluded that office administration students are better than travel agency students in speaking.Keywords: pronunciation error, long vowels, speaking test